Effect of sanitation on responses of Tribolium castaneum (herbst) (Coleoptera: tenebrionidae) life stages to structural heat treatments - Brijwani, Monika (Kansas State University, 2011)
Heat treatment involves raising the ambient temperature of food-processing facilities such as flour mills to 50-60oC for killing stored-product insects. However, very little is known about the influence of sanitation on responses of stored-product insects to structural heat treatments. The impact of sanitation on responses of life stages of the red flour beetle, Tribolium castaneum, an economically important pest in flour mills, were investigated during three 24 h structural heat treatments of the Kansas State University pilot flour mill. Two sanitation levels, dusting of wheat flour (~0.5 g) and 2-cm deep flour (~43 g), were created in 25 plastic bioassay boxes each holding 50 eggs, 50 young larvae, 50 old larvae, 50 pupae, and 50 adults of T. castaneum in separate compartments. Five boxes were placed on each of five floors of the pilot mill during 13-14 May 2009, 25-26 August 2009, and 7-8 May 2010 heat treatments using forced air gas heaters. During the August 2009 and May 2010 heat treatments, 100 eggs or 100 adults of T. castaneum were exposed inside each 20 cm diameter by 15 cm high PVC ring placed only on first and third floors and holding 0.1 (15 g), 0.2 (38 g), 1 (109 g), 3 (388 g), 6 (937 g), or 10 (1645 g) cm deep wheat flour. Among the mill floors, first floor had lower maximum temperature. The first floor rests on a thick concrete foundation, did not get heated from both sides unlike other floors, and had poor air movement resulting in cold pockets (temperatures <50oC). Mortality of life stages was lower on first floor than other floors and adults were less susceptible than other life stages especially on first floor. In general, both these tests have shown that the mortality of T. castaneum life stages were influenced by how quickly temperatures reached 50oC, how long temperatures were held above 50oC, and the maximum temperature. Protective effects of sanitation were evident only if temperatures did not reach 50oC. However, removal of flour accumulations is essential to improve heat treatment effectiveness against all T. castaneum life stages during a 24 h treatment.
Keywords: heat treatment; sanitation; insect mortality; red flour beetle; methyl bromide alternatives; Food Science (0359)